ANALISIS PENGARUH DAERAH ASAL SMA TERHADAP NILAI UJIAN MAHASISWA DENGAN MENGGUNAKAN UJI WALD-WOLFOWITZ - Rola M. Lendert; S. N. Aulele; Y. A. Lesnussa (VARIANCE: Journal of Statistics and Its Applications, 2019)
Origin is a factor that influences one's behavior about the value of the Mathematics Student's exam that comes from the Ambon city area and outside the city of Ambon. In this research, the method used to look at two independent samples is the Wald-Wolfowitz Test in the academic year 2016/2017. The purpose of this study to determine the influence of the origin of high school to the value of the middle exam of Elementary Linear Algebra in Department Mathematics FMIPA Unpatti. The result shows that there is no difference in the middle exam of Elementary Linear Algebra value between students who are in Ambon city and students who are outside Ambon city.